2009
DOI: 10.1152/ajpendo.90931.2008
|View full text |Cite
|
Sign up to set email alerts
|

High doses of dexamethasone induce increased β-cell proliferation in pancreatic rat islets

Abstract: Here, we report a model to study ␤-cell proliferation in living rats by administering three different doses of dexamethasone (0.1, 0.5, and 1.0 mg/kg ip, DEX 0.1, DEX 0.5, and DEX 1.0, respectively) for 5 days. Insulin sensitivity, insulin secretion, and histomorphometric data were investigated. Western blotting was used to analyze the levels of proteins related to the control of ␤-cell growth. DEX 1.0 rats, which present moderate hyperglycemia and marked hyperinsulinemia, exhibited a 5.1-fold increase in ␤-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
153
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(172 citation statements)
references
References 48 publications
18
153
1
Order By: Relevance
“…The islet compensatory response is also accompanied by structural changes. It has been demonstrated that, b-cell mass increases in a time- (Rafacho et al 2011) and dose-dependent manner (Rafacho et al 2009) with GC administration, according to the correspondent degree of insulin insensitivity. Taken together, these results show that when humans or animal models are exposed to prolonged steroid treatment, they develop augmented b-cell function and mass to counteract the IR resulting from GC administration.…”
Section: Figurementioning
confidence: 99%
“…The islet compensatory response is also accompanied by structural changes. It has been demonstrated that, b-cell mass increases in a time- (Rafacho et al 2011) and dose-dependent manner (Rafacho et al 2009) with GC administration, according to the correspondent degree of insulin insensitivity. Taken together, these results show that when humans or animal models are exposed to prolonged steroid treatment, they develop augmented b-cell function and mass to counteract the IR resulting from GC administration.…”
Section: Figurementioning
confidence: 99%
“…To study β-cell mass and cellular distribution of Pdx-1, the endocrine pancreas was excised from 4 animals in each group and processed as previously described (19)(20)(21). The relative and absolute β-cell mass as well as the islet number per pancreatic area were determined by point-counting morphometry on each pancreas section immunostained for Table 1.…”
Section: Islet Area β-Cell Mass and Pdx-1 Cellular Distributionmentioning
confidence: 99%
“…Islet protein (100 µg) was used for each experiment as previously reported (20,21). Immunoblotting experiments were performed at least five times.…”
Section: Tissue Extraction and Immunoblottingmentioning
confidence: 99%
“…In healthy humans, it has been reported that insulin secretion is two-to fourfold increased to compensate increased insulin resistance after short-term GC administration (21)(22)(23). In rodents, GC administration has been shown to promote an increase in BCM and in insulin secretion through an increase in b-cell replication and b-cell neogenesis (18)(19)(20). On the basis of these previous studies, we hypothesized that BCM might also be increased in humans who received GC therapy.…”
mentioning
confidence: 96%
“…As a result, the use of GCs is associated with a risk of development or worsening of glucose intolerance, which is well known as one of the major adverse effects of GC therapy (17). In rodents, GC-induced insulin resistance was shown to increase insulin biosynthesis and secretion and promote BCM expansion through b-cell proliferation (18)(19)(20). GC administration in humans has also been shown to augment insulin secretion (21)(22)(23); however, the effect of GC therapy on BCM in humans is unknown.…”
mentioning
confidence: 99%